Drug Users' Resilience During Rehabilitation is Strengthened Through Family Support, Personal Coping Skills, and Structured Programs Offering Diverse Therapeutic Interventions - Ayu Nur Chandra Lestari; I Nyoman Suyatna; Luh Nyoman Alit Aryani (Indonesian Journal of Global Health Research, 2025)
Historically, addiction treatment in the early 20th century emphasized punitive responses and abstinence-based models, often neglecting the underlying psychological and environmental contributors to substance use. In recent decades, a more holistic and integrative understanding of SUDs has emerged—one that acknowledges the significance of psychosocial dimensions in both the etiology and recovery processes. Resilience plays a critical role in the recovery process of individuals undergoing drug rehabilitation. The research employed a literature review design using a comprehensive strategy. Articles were sourced from international research journal databases accessed via the internet, specifically ScienceDirect, PubMed, and Google Scholar. All searches were conducted in May-June 2025. The keywords used in this literature review were adapted from the Medical Subject Heading (MeSH) terms, including "drugs user resilience” “rehabilitation” “family support” and “legal and coping skills. The initial search yielded 500 results, of which 5 were duplicates. Hand-searching relevant journal articles added one unique article. Of the 260 remaining results, 40 were retained after a title and abstract review. Following a full-text review, 40 articles were included in the study. A PRISMA flowchart outlining the search process. Family support emerged as a strong predictor of resilience. Several reports indicate that emotional regulation, self-acceptance, and secure coping skills correlate with higher resilience scores, while structured rehabilitation programs with multidisciplinary teams and institutional support appear to foster improved outcomes. Interventions such as expressive arts therapy, group counseling based on established models, and combined cognitive-behavioral/mindfulness approaches were associated with positive changes in resilience measures.